Effects of Recycled Expanded Polystyrene Beads on the Mechanical and Physical Properties of Cement-Stabilized Compressed Earth Bricks - Géraldine Gouafo Kougoum; Ulrich Giresse Defo Tatchum; Bernard Morino Ganou Koungang; Dieunedort Ndapeu; René Tchinda (Advances in Civil Engineering)
Nowadays, research on environmentally friendly materials has become a significant challenge in the field of civil engineering. In this study, stabilized compressed earth bricks (CEBs) incorporating recycled expanded polystyrene (EPS) beads were studied with the aim of enhancing the development of green constructions. The mass contents of recycled EPS in CEB formulated at a compaction pressure of 5 MPa are 0%, 0.25%, 0.5%, 0.75%, and 1% relative to the mass of the soil, while cement type CEM I 32.5, as a stabilizer, constituted 8% by mass. Characterization was carried out by determining densities, dry and wet compressive strength, flexural strength, total water absorption, and capillarity. Sample properties were found to be strongly influenced by the percentage of recycled EPS. Increasing the EPS aggregate content led to a reduction in compressive strength in both wet and dry conditions. Samples with 0.5% EPS and 8% cement offered better physical and mechanical performance. Samples containing EPS had relatively low water absorption, which would contribute to good durability. These CEBs comply with the wall construction requirements for two-story dwellings. This study also demonstrates the potential use of this recycled material in the construction industry.